Krabbe Disease in the Arab World - Zayed, Hatem (Journal of Pediatric Genetics, 2015)
The autosomal recessive inherited Krabbe disease (KD) is a devastating pediatric lysosomal storage disorder affecting white matter of the brain. It is caused by mutations in the gene coding for the lysosomal enzyme galactocerebrosidase. While most patients present with symptoms within the first 6 months of life, others present later in life throughout adulthood. The early infantile form of KD (EIKD) is frequent in the Muslim Arab population in Israel, with a very high prevalence of approximately 1/100 to 1/150 live births. The homozygous variant c.1582G > A (p.D528N) was found to be responsible for EIKD in Palestinian Arab patients. KD was reported in different Arab countries with much lower frequency. While most Arab patients presented with EIKD, late infantile and late onset KD forms were also reported. Most Arab patients presented with variable symptoms ranging from EIKD to late onset KD, with variable clinical findings. Based on literature studies, this review focuses on the clinical and molecular findings of KD patients with Arab ancestry, and highlights the need for developing universal genetic screening programs to overcome the under-reported status of KD prevalence in Arabia. This is expected to improve the prognosis of the disease and promote targeted molecular diagnostics to the Arab patients.
Keywords: Krabbe disease; galactocerebrosidase; genotype–phenotype correlation; Arabs; prenatal diagnosis